Propriedades estruturais de géis de sílica preparados com adições de dodecil sulfato de sódio - Perissinotto, Amanda Pasquoto [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
This work aims to study the structural characteristics of silica gels obtained from the acid hydrolysis of tetraethoxysilane (TEOS) in water solutions with different concentrations of sodium dodecyl sulfate (SDS). The structural characteristics were studied in stages ranging from the wet gel to the dry stages of the gels (aerogels and xerogels). Aerogels were obtained by ambient pressure drying (APD) after silylation process using trimethylchlorosilane (TMCS) as silylating agent. Xerogels were obtained by conventional evaporating the liquid phase from non silylated gels. The samples were characterized by nitrogen adsorption and small angle X-ray scattering (SAXS). The structure of the wet gels and of the aerogels prepared with the surfactant exhibited characteristics of mass-fractal structures with fractal dimension D in the range 2.1-2.2 for the wet gels and 2.3-2.4 for the aerogels. The characteristic size  of the fractal domain reduces while the size a0 of the primary silica particle composing the fractal structure increases with the drying of the gels, in a process in which share of the porosity is eliminated. Aerogels exhibited typical values for the specific surface of 900 m2g-1 and of 3.5 cm3.g-1 for the total pore volume. These values are correspondingly comparable to those of the aerogels prepared by supercritical drying, since the silylation process replaces hydrophilic –OH groups by hydrophobic –Si-R3 ones, inhibiting the porosity elimination on drying. The silica particle size also increases lightly with the silylation because the attachment of the –Si-R3 groups on the silica surface. The pore size distribution curves of the aerogels are similar for all samples exhibiting a maximum in around 40 nm, independent the concentration of surfactant. This suggests that the characteristic size of 40 nm is due to the association of surfactant micelles... (Complete abstract click electronic access below)

O presente trabalho objetiva estudar as características estruturais de géis de sílica obtidos a partir da hidrolise ácida do tetraetilortosilicato (TEOS) em solução aquosa preparada com diferentes concentrações do surfactante aniônico Dodecil Sulfato de Sódio (SDS). As características estruturais são estudadas em estágios que vão desde o gel úmido até os estados secos do gel (aerogel e xerogel). Aerogéis foram preparados por secagem a pressão ambiente (APD) depois de sililação em fase úmida, usando trimetilclorosilano (TMCS) como agente sililante. Xerogéis foram obtidos por evaporação convencional da fase líquida nos géis não sililados. As amostras foram caracterizadas por adsorção de nitrogênio e espalhamento de raios-X a baixo ângulo (SAXS). A estrutura dos géis úmidos e dos aerogéis preparados com o surfactante apresentaram características de estruturas fractais de massa com dimensão fract al D no intervalo 2,1-2,2 para os géis úmidos e 2,3-2,4 para os aerogéis. O tamanho característico  do domínio fractal se reduz enquanto o tamanho a0 da partícula primária de sílica que compõe a estrutura fractal aumenta com a secagem dos géis, num processo onde parte da porosidade é eliminada. Os aerogéis apresentaram valores típicos de 900 m2/g para superfície específica e 3,5 cm3/g para o volume total de poros. Esses valores são correspondentemente comparáveis com aqueles de aerogéis preparados por processo supercrítico, uma vez que o processo de sililação substitui os grupos hidrofílicos –OH por grupos hidrofóbicos –Si-R3, inibindo a eliminação da porosidade na secagem. O tamanho das partículas de sílica também aumentam ligeiramente com a sililação por causa da fixação dos grupos –Si-R3 na superfície da sílica. As curvas de distribuição de tamanho de poros dos aerogéis são bastante parecidas e apresentam... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Física aplicada; Processo sol-gel; Adsorção; Nitrogenio; Silica gel; Sulfato de sodio